1998
DOI: 10.1128/mcb.18.8.4807
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Transcriptional Regulation by LEF-1 in Response to Wnt-1 Signaling and Association with β-Catenin

Abstract: Wnt signaling is thought to be mediated via interactions between ␤-catenin and members of the LEF-1/TCF family of transcription factors. Here we study the mechanism of transcriptional regulation by LEF-1 in response to a Wnt-1 signal under conditions of endogenous ␤-catenin in NIH 3T3 cells, and we examine whether association with ␤-catenin is obligatory for the function of LEF-1. We find that Wnt-1 signaling confers transcriptional activation potential upon LEF-1 by association with ␤-catenin in the nucleus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
350
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(375 citation statements)
references
References 76 publications
22
350
0
1
Order By: Relevance
“…Cartilage extracts containing FRZB have in vivo chondrogenic activity. [31][32][33] In our study, FRZB was down-regulated in OA synovium and cartilage and in RA cartilage. Therefore, FRZB might be also involved in human joint cartilage destruction.…”
Section: Discussionmentioning
confidence: 70%
“…Cartilage extracts containing FRZB have in vivo chondrogenic activity. [31][32][33] In our study, FRZB was down-regulated in OA synovium and cartilage and in RA cartilage. Therefore, FRZB might be also involved in human joint cartilage destruction.…”
Section: Discussionmentioning
confidence: 70%
“…We and others have demonstrated that Wnt-1 or Dvl1, when expressed in NIH3T3 cells, can activate the transcription regulator 16,28,29). This activation depends on β-catenin and is suppressed by GSK-3β and axin.…”
Section: Dep Domain Interacts With Upstream Regulators Of Dvlmentioning
confidence: 79%
“…To directly test whether PTEN could affect TCF transcription activity, we examined the PTEN influence on the activity of a LEF-1-luciferase reporter, which contains classical LEF-1-binding sites (Hsu et al, 1998). As shown in Figure 4f, exogenous expression of PTEN in Pten-null MEFs reduced the LEF-mediated (Figure 5a), and previous studies have shown that CREB can bind to this CRE (Sicinski et al, 1996).…”
Section: Suppression Of Cyclin D2 Expression By Pten W Huang Et Almentioning
confidence: 94%